Perioral rejuvenation: restoration of attractiveness in aging females by minimally invasive procedures - Wollina U (Dove Medical Press, 2013)
Uwe Wollina Department of Dermatology and Allergology, Academic Teaching Hospital Dresden-Friedrichstadt, Dresden, Germany Abstract: Lips and the perioral area are of outstanding importance in youthful appearance, attractiveness, and beauty. In contrast to younger and middle aged females, there is only scant published data on minimally invasive procedures to restore and revitalize lips and perioral soft tissue in elderly females. In this review we report the signs of aging in this particular region and the underlying anatomy. We review studies on lip restoration in younger females and present our techniques for elderly women. With an individually tailored approach, elderly females benefit from minimally invasive techniques. Keywords: facial aging, perioral soft tissue, lips, dermal fillers, anatomy